Tingkat Kepuasan Wisatawan NusantaraTerhadap Layanan Penjualan Hortikultura di Pasar Mertha Sari Desa Candikuning Kabupaten Tabanan - NIRMALASARI, SAGUNG DIAH; DIARTA, I KETUT SURYA; SARJANA, I MADE (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.5, No.1, Januari 2016, 2016)
Abstract Satisfaction Level of Domestic Tourists upon Horticulture Products in Candikuning Tourism Village Tabanan Regency A raise in the number of tourism spots in Tabanan regency has brought its own challenges. In order to encourage tourists to purchase local products, a tourism spot has to have a certain attraction which identifies it among the other tourism spots. Candikuning is a tourism village in Tabanan regency which is recognized for its plentiful variety of agriculture products marketed at Pasar Mertha Sari (Mertha Sari Traditional Market). The objective of this research is to identify the dominant horticulture products that the tourists purchased/ consumed at Pasar Mertha Sari, and to study the satisfaction level of domestic tourists upon horticulture products planted by local farmers in Candikuning village. The data used in this research was obtained from observation, survey, interview, literature study and documentation which further analyzed using descriptive-qualitative method. The result shows that strawberries are dominant horticulture product consumed by tourists (14.44%). This number signifies a dependable potential of strawberry farming to support the horticulture farming business. In the other hand, the satisfaction level reached average score of 3.85 (77.15%) which indicates that tourists’ satisfaction level is in the level of satisfied in terms of product quality, price, public facility, location, service, security and comfort. Several improvements in this tourism spot are required so that the tourists could reach higher satisfaction level especially in service, facility, reliability of product supply, product affordability, security, and comfort. In addition, upgrades are required for the shop itself where buyers and sellers met. The improvements are expected to attract more consumers to purchase and consume horticulture products planted in Candikuning village. Keywords: Satisfaction level, domestic tourists, horticulture, tourism spot